2023
DOI: 10.1093/eurjpc/zwad036
|View full text |Cite
|
Sign up to set email alerts
|

Remnant cholesterol, low-density lipoprotein cholesterol, and incident cardiovascular disease among Koreans: a national population-based study

Abstract: Background and Aims The synergistic association of remnant cholesterol (remnant-C) and low-density lipoprotein cholesterol (LDL-C) levels with incident cardiovascular disease (CVD) in various subgroups of Koreans was investigated. Methods Using the national health insurance data, we included subjects aged between 40 and 70 without a history of CVD and at least two health screenings between 2009 and 2011. The subjects were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Overall, the results of recently published observational and genetic Mendelian randomization studies support a causal association between elevated remnant cholesterol and ASCVD (Table 1) [20 ▪▪ ,22 ▪▪ ,23–25,26 ▪ –28 ▪ ,29–32,33 ▪ ,34–39]. Furthermore, the results imply that remnant particles have a substantially greater per particle atherogenicity than LDL, most probably because remnants per particle carry substantially more cholesterol than LDL [20 ▪▪ ,21] (Fig.…”
Section: Recent Evidencementioning
confidence: 58%
“…Overall, the results of recently published observational and genetic Mendelian randomization studies support a causal association between elevated remnant cholesterol and ASCVD (Table 1) [20 ▪▪ ,22 ▪▪ ,23–25,26 ▪ –28 ▪ ,29–32,33 ▪ ,34–39]. Furthermore, the results imply that remnant particles have a substantially greater per particle atherogenicity than LDL, most probably because remnants per particle carry substantially more cholesterol than LDL [20 ▪▪ ,21] (Fig.…”
Section: Recent Evidencementioning
confidence: 58%
“…According to Huh et al, 14 elevated levels of remnant cholesterol (≥ 30 mg/dL) are associated with CVD incidence in adults with type 2 diabetes, independent of LDL-C levels. Lee et al 15 have likewise demonstrated an association between calculated fasting remnant cholesterol and ischemic heart disease or stroke in previously asymptomatic South Korean subjects.…”
Section: Role Of Trls In Ascvdmentioning
confidence: 84%
“…Using the Korean National Health Insurance Service database of 1 956 452 patients with type 2 diabetes mellitus without prior cardiovascular disease, Huh et al [22] showed a 22–28% increased risk of ischemic stroke and MI in patients in the top quartile of remnant cholesterol compared to the lowest quartile. In a subsequent publication from the same database, Lee et al [23 ▪▪ ] focused on a general population of 3 686 034 individuals (45.6% women), and confirmed the association of remnant cholesterol with cardiovascular events independent of LDL-C or other conventional risk factors.…”
Section: Pathophysiology Of Elevated Remnant Cholesterol and Cad Due ...mentioning
confidence: 86%